Alteration in angiotensin-converting enzyme 2 by PM1 during the development of emphysema in rats. Issue 4 (5th October 2020) - Chuang, Hsiao-Chi; Chen, Yi-Ying; Hsiao, Ta-Chih; Chou, Hsiu-Chu; Kuo, Han-Pin; Feng, Po-Hao; Ho, Shu-Chuan; Chen, Jen-Kun; Chuang, Kai-Jen; Lee, Kang-Yun
Introduction: Angiotensin-converting enzyme 2 (ACE2) provides an adhesion site for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Patients with COPD could have severe outcomes after SARS-CoV-2 infection. The objective of this study was to investigate ACE2 regulation by air pollution during the development of COPD. Methods: Sprague Dawley rats were exposed to unconcentrated traffic-related air pollution for 3 and 6 months. We examined lung injury markers, oxidative stress, inflammation, emphysema, ACE2 and angiotensin II receptor type 1 (AT1) and 2 (AT2) in the lungs after exposure. Results: Lung injury occurred due to an increase in permeability and lactate dehydrogenase cytotoxicity was observed after 6 months of exposure to fine particulate matter of <1 μm in aerodynamic diameter (PM1 ). An α1 -antitrypsin deficiency and neutrophil elastase production with emphysema development were observed after 6 months of PM1 exposure. 8-isoprostane and interleukin-6 were increased after 3 and 6 months of PM1 exposure. Caspase-3 was increased after exposure to PM1 for 6 months. Upregulation of ACE2 was found after 3 months of PM1 exposure; however, ACE2 had decreased by 6 months of PM1 exposure. AT1 and AT2 had significantly decreased after exposure to PM1 for 6 months. Furthermore, smooth muscle hypertrophy had occurred after 6 months of PM1 exposure. Conclusions: In conclusion, short-term exposure to PM1 increased the ACE2 overexpression in lungs. Long-term exposure to PM1 decreased the ACE2 overexpression in emphysema. Air pollution may be a risk for SARS-CoV-2 adhesion during the development of COPD. Short-term exposure to PM1 increases ACE2 overexpression in lungs. Long-term exposure to PM1 decreases the ACE2 overexpression in emphysema. Air pollution may be a risk for #SARSCoV2 adhesion during the development of COPD. https://bit.ly/2Vfykur